PHYSICO-CHEMICAL STUDY ON THE MATRICARIA CHAMOMILLA AND ALOE BARBADENSIS SPECIES AND MEDICAL IMPLICATIONS - Olimpia Dumitriu Buzia; Costache (Gheorghe); Gabi Topor; Sergiu Ciprian Focsaneanu; Nechifor Alexandru; Ionuța Grigore; Elena Laura Parapiru; Rodica Mihaela Dinica (Romanian Society of Oral Rehabilitation, 2022)
In the present paper, we followed the botanical and phytochemical characterization of the two plants Matricaria Chamomilla and Aloe Barbadensis, known since antiquity. We performed the spectrophotometric analysis of some compounds from the structure of the two plants, we studied the antioxidant activity in order to scientifically validate the therapeutic effects and the subsequent possibility of obtaining pharmaceutical preparations with possible anti-acne, healing, anti-inflammatory actions.